AB0103 Identification of Synovial Fluid Micrornas as Potential OA Biomarkers. (9th June 2015) - Li, Y.-H.; Gandhi, R.; Veillette, C.; Weston, A.; Perry, K.; Antflek, D.; Perruccio, A.; Davey, R.; Syed, K.; Mahomed, N.; Kapoor, M.
Abstract : Background: MicroRNAs (miRNAs) are a novel class of non-coding small RNAs. They are 19-22 nucleotides in length and negatively regulate gene expression through mRNA cleavage or translation suppression. miRNAs have been implicated in various physiological and pathological conditions including OA. OA is a chronic degenerative disease characterized by cartilage degradation, subchondral bone remodelling and synovial inflammation. Identification of OA biomarkers is critical as current image-based detection is of suboptimal accuracy and sensitivity. The presence and high stability of circulating miRNAs in synovial fluid make them attractive as potential OA biomarkers. Objectives: The objectives of our study were, (1) To identify differentially expressed miRNAs in synovial fluid from endstage OA patients compared to early-stage OA patients, and (2) To explore the use of these differentially expressed miRNAs as potential OA biomarkers. Methods: miRNA profiling of knee synovial fluid from 4 endstage (patients scheduled to undergo knee replacement surgery for OA) and 4 early-stage (patients undergoing arthroscopic surgery for knee OA) OA patients was undertaken using miRCURY LNA Universal RT microRNA PCR Human panel I+II arrays. Validation work was based on knee synovial fluid samples from 27 endstage OA and 24 early-stage OA patients. Quantitative real-time PCR was used for validation. Results: The miRCURY LNA PCR arrays contained 752 miRNAs and we identified 14 differentially expressed miRNAs in end stage OA compared to early-stage OA. Among these, expression of three miRNAs (miR-27a-3p, miR-378 and miR-101) was only detected in endstage OA, six miRNAs (miR-23a, miR-24, miR-29c, miR-34a, miR-186, miR-27b) were up-regulated and five miRNAs (miR-934, miR-329, miR-655, miR-27a-5p and miR-708-3p) were down-regulated. At second stage of the study, we validated the expression of these 14 miRNAs. Nine miRNAs (miR-23a, miR-24, miR-29c, miR-34a, miR-186, miR-27b, miR-27a-3p, miR-27a-5p and miR-378) remained significantly differentially expressed irrespective of gender. Specifically, miR-378 was detected in majority of endstage OA but rarely in early stage OA synovial fluid. Conclusions: We identified and validated 9 miRNAs differentially expressed in knee synovial fluid in endstage compared to early-stage knee OA patients. Importantly this is the first study to profile miRNA expression in OA synovial fluid and 3 miRNAs identified in our study have never been reported to be associated with OA. Current work is underway investigating the source of these miRNAs and if the identified miRNAs exhibit any pathophysiological role in OA. Based on the current data, these miRNAs have the potential to serve as minimally invasive OA biomarkers. Acknowledgements: This work is supported by Dr. Kapoor's Start-up funds provided by the UHN Arthritis Program, Toronto Western Research Institute, Toronto Western Hospital. Disclosure of Interest: None declared